Prosedur Penerapan Sistem Manajemen Keselamatan (SMK) di atas kapal MT. Garuda Asia pada PT. Pelayaran Multi Jaya Samudera Belawan - Girsang, Jandri William; Ginting, Dafid (Innovative: Journal Of Social Science Research, 2024)
This article aims to find out the Procedures for Implementing a Safety Management System (SMK) on MT ships. Garuda Asia at PT. Multi Jaya Samudera Belawan Delivery. In writing this paper the author used a methodology, during carrying out Land Practices (PRADA), the author also collected materials from field methods (Field Research) and library methods (Library Research) to find out more closely how the company PT. Pelayaran Multi Jaya Samudera Belawan in improving the safety of MT crew members. GarudaAsia. The Safety Management System is a facility for all personnel on land and at sea to implement all company policies in the field of safety. Everything will go well if the Safety Management System (SMK) Implementation Procedure runs well. Safety in this case includes the ship, crew, cargo and marine environment. PT. Pelayaran Multi Jaya Samudera Belawan is a shipping company that prioritizes service and safety as its main priority. The abstract consists of 150-200 words, containing a brief description of the research problem and objectives, methods used, and research results. The pressure for writing abstracts is mainly on research results.